Pemikiran Abdullah An – Naim: Tentang Pendidikan Islam HAM dan Islam Sekuler - Robit Robit; Ubaidillah Ubaidillah; Hepni Hepni; Dyah Nawangsari (Program Studi Pendidikan Agama Islam STAI Sayid Mohammad Alawi Al Maliki, 2025)
Abdullah An Naim is one of the prominent figures in the field of Islamic education. His various works are widely studied in different countries, including his monumental work on secular Islam and human rights. One of the objectives of this research is to analyze Abdullah An Naim's thoughts on human rights and secular Islam within the context of Islamic education. This type of research is a literature study with a historical-philosophical approach. Data collection refers to documentation and literature from books, journals, and lectures. The results of this research indicate that An Naim emphasizes a historical and sociological approach to secular Islam, reinterpreting the comprehensive meaning of Islam without separating Islamic teachings from modern ideas about human rights.